1999
DOI: 10.1271/bbb.63.309
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Serum Lipids and Aortic Lesion Size in Female and Male Apo E-Deficient Mice Fed Docosahexaenoic Acid

Abstract: Apolipoprotein (apo) E-deficient mice were fed an atherogenic diet with either 1% ethyl ester docosahexaenoic acid (DHA) or safflower oil (SO) as a source of linoleic acid for 8 week. Both genders fed DHA had higher proportions of eicosapentaenoic acid and DHA, and lower proportions of linoleic and arachidonic acids in the liver and serum phospholipids than those fed SO. Males fed DHA had greater liyer weight and tended to haye higher concentrations of serum lipids and liyer cholesterol than those fed SO, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
(2 reference statements)
2
13
3
Order By: Relevance
“…In contrast to previous observations [2,24], fish oil and n-3 fatty acid ethyl esters caused great decreases in serum cholesterol, triacyglycerol, and phospholipid levels in apoEdeficent mice in the present study. The levels in the animals fed fish oil and n-3 fatty acid ethyl esters dropped to less than 30% and 50%, respectively, of the values in the animals fed palm oil.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to previous observations [2,24], fish oil and n-3 fatty acid ethyl esters caused great decreases in serum cholesterol, triacyglycerol, and phospholipid levels in apoEdeficent mice in the present study. The levels in the animals fed fish oil and n-3 fatty acid ethyl esters dropped to less than 30% and 50%, respectively, of the values in the animals fed palm oil.…”
Section: Discussioncontrasting
confidence: 99%
“…We hypothesized that apoE expression is required for n-3 fatty acid-dependent regulation of hepatic fatty acid metabolism, and a disturbance in the regulation of the metabolic pathway may account for the failure of fish oil to reduce serum lipid levels in apoE-knockout (Apoe tm1Unc ) mice observed in previous studies [2,24]. To address this point, we used an alternative apoE-deficient model (BALB/ c.KOR-Apoe shl mice) that we have developed [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, these fish oil derived n-3 PUFA have been shown to be atheroprotective in different mouse models of the disease [12][13][14][15][16], to reverse defective efferocytosis of apoptotic cells in obese mice [17], to enhance atherosclerotic plaque stability in humans awaiting carotid endarterectomy [18] and to be effective in reducing the risk of cardiac mortality [19,20]. Nevertheless, despite this evidence, other studies have contradicted some of these results [21][22][23] although this could be linked to background levels of n-6 PUFA since these can affect the efficacy of n-3 PUFA in atheroprotection [24] and since lowering the n-6:n-3 PUFA ratio in ApoE -/-mice reduces atherosclerotic plaque development [16]. Some of the atheroprotective effects of n-3 PUFA in mice have been shown to involve changes in macrophage function [12,17] and a recent study found that EPA, delivered from n-3 PUFA ethyl esters, reduced foam cell accumulation in advanced human carotid plaques [25] suggesting that n-3 PUFA not only target macrophage activity but also foam cell formation.…”
Section: Introductionmentioning
confidence: 99%